Oohhaa! Kamek Orang Sarawak: A Glimpse into Sarawakians’ Diverse Perspectives on What It Means to be Sarawakian - Jerome, Collin; Ting, Su-Hie (Kajian Malaysia, 2026)
‘Sarawakian’ identity continues to be a topic of active discussion both within Malaysia and internationally. While these debates have brought Sarawakians into the spotlight, there is a pressing need for a deeper understanding of the complex nature of Sarawakian identity, which is often limited by narrow perspectives. This article seeks to expand our understanding of how Sarawakians define and perceive the terms Sarawakian and Sarawakian identity. To explore this, we surveyed 311 participants from diverse backgrounds within Sarawak and used thematic analysis to identify key interpretations of these terms. Our analysis revealed 13 distinct themes. Participants defined Sarawakian in relation to culture, diversity, and heritage, while Sarawakian identity was linked to cultural pride and a strong connection to the region. Importantly, our findings highlight the multifaceted role of Sarawakian identity, not only as a tool for self-classification but also as a crucial aspect of participants’ collective identity. These insights are especially relevant given the growing ‘Sarawak for Sarawakian’ sentiment, which is fueled by ongoing calls for greater autonomy. Our study contributes to a deeper understanding of Sarawakian identity, particularly in the context of recent political developments.